2019
DOI: 10.21149/9996
|View full text |Cite
|
Sign up to set email alerts
|

Porcentaje de grasa corporal en adolescentes asociado con conductas alimentarias de riesgo, hogar y sexo

Abstract: Objetivo. Determinar la asociación de las conductas ali­mentarias de riesgo (CAR) y el hogar con el porcentaje de grasa corporal (PGC) en los adolescentes, modificado por sexo. Material y métodos. Se analizó la información de una cohorte de 2 388 adolescentes de Morelos, México, de 2004 a 2007. Se realizaron técnicas descriptivas y modelos de regresión lineal múltiple de efectos mixtos. Resultados. El cambio del PGC es -1.4 puntos porcentuales (EE 0.22), en hombres -3.1 (EE 0.35) y en mujeres 0.2 (EE 0.21). El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
2
0
3
Order By: Relevance
“…With regards to personality patterns, individuals who have previously followed or currently follow dangerous weight loss diets tend to also be those with the highest scores in variables such as neuroticism, obsession with thinness, bulimia, body dissatisfaction and asceticism. They also reveal traits of perfectionism, emotional negativity, symptoms of depression, low self-esteem and negative impulsiveness [ 64 ]. In terms of the aforementioned personality traits (perfectionism, obsession with thinness, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…With regards to personality patterns, individuals who have previously followed or currently follow dangerous weight loss diets tend to also be those with the highest scores in variables such as neuroticism, obsession with thinness, bulimia, body dissatisfaction and asceticism. They also reveal traits of perfectionism, emotional negativity, symptoms of depression, low self-esteem and negative impulsiveness [ 64 ]. In terms of the aforementioned personality traits (perfectionism, obsession with thinness, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the highest percentages of the sample-more than a third of the females and a little more than half of the males-were normal weight (Table 1), and although it can be said that the sample was at risk of obesity (a quarter of the males and an eighth of the females were overweight), in reality, very low percentages of obesity were found (less than five percent) [56,57]. On the other hand, regarding the sexual orientation of the boys/girls in the sample, it was found that more than a third of the boys and girls responded that they were heterosexual.…”
Section: Discussionmentioning
confidence: 65%
“…Datos parecidos se encontraron en la investigación de Quintero, González, Gutiérrez, Puga y Villanueva (17) en donde las CAR como desayunar ocasionalmente (1,4 veces) y percibirse más delgado (2,5 veces) muestra mayor índice de riesgo. De la misma manera en el estudio de Sánchez, Flores y Lazcano (18) se encontró que el hacer dieta para bajar de peso sin la supervisión médica tuvo mayor índice de riesgo. Por lo dicho, se determina que las conductas alimentarias muestran un índice de riesgo alto de presentarse en los adolescentes.…”
Section: Discussionunclassified